Characterizing subsidence in used and restored peatland with Sentinel SAR data - Tarigan, Suria; Kristanto, Yudha; Utomo, Waluyo Y. (Frontiers in Environmental Science, 2023)
Peatland is a fragile ecosystem in the tropical region which is prone to subsidence. Until now, there is still lack of procedure to rapidly assess a tropical peatland subsidence in a large area. Our objective was to compare subsidence in a used and restored zone in a peatland hydrological unit using synthetic aperture radar data from Sentinel-1A products (SAR data) in South Sumatra, Indonesia from the period of 2014-2021.The subsidence rate of used peatland estimated by the D-InSAR procedure were in the range of 28-80 cm year -1 in the early period of its utilization and becoming less for the consecutive year (16-48 cm year -1 ). Meanwhile, the subsidence rate based on the field surveys was in the range of 4-50 cm year -1 in the early period of peatland utilization. The subsidence rate in the used peatland zone (agriculture and plantations) was higher than that in the restoration zone for all SAR data pairs used in our study. The SAR data is a potential tool for the assessment, monitoring and differentiating subsidence rates among different peatland uses in a large area. This tool will help the Directorate of Peat Ecosystem Degradation Control, Directorate General of Environmental Pollution and Degradation Control, and Ministry of Environment and Forestry to plan for better peatland management and restoration.Peatland in Indonesia covers 13.9 million ha, being mostly located in Sumatra, Kalimantan, and Papua. Some peatlands in Indonesia are used for agriculture and plantation purposes, potentially accelerating their oxidation and decomposition processes. The continual oxidation and decomposition of peatlands can result in substantial land subsidence (Gambolati et al., 2005), and cumulative subsidence can reach Deleted: The peatland in Indonesia covers 13.9 million ha, being 38 mostly located in Sumatra, Kalimantan, and Papua. Some peatlands 39 in Indonesia are used for agriculture and plantations, which can 40 accelerate their oxidation and decomposition processes. Continuous 41 oxidation and decomposition can lead to substantial peatland 42 subsidence, and continuous land subsidence can lead to a loss of land, 43 meaning a loss of future peatland ecosystem services, such as climate 44 and water regulations.